2012
DOI: 10.1104/pp.111.191288
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Indole-3-Butyric Acid and Indole-3-Acetic Acid in Arabidopsis Hypocotyls Using Stable Isotope Labeling      

Abstract: The polar transport of the natural auxins indole-3-butyric acid (IBA) and indole-3-acetic acid (IAA) has been described in Arabidopsis (Arabidopsis thaliana) hypocotyls using radioactive tracers. Because radioactive assays alone cannot distinguish IBA from its metabolites, the detected transport from applied [ ]IAA was found in the basal end. Our results demonstrate that the polar transport of IBA is much lower than IAA in Arabidopsis hypocotyls, and the transport mechanism is distinct from IAA transport. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 57 publications
3
32
0
1
Order By: Relevance
“…Independent IAA and IBA transport catalysts are also supported by the finding that neither NPA nor the competitive auxin inhibitor, TIBA (2,3,5-triiodobenzoic acid), blocks IBA transport (Rashotte et al 2003, Liu et al 2012. Genetic approaches in Arabidopsis support the idea that IBA efflux from root cells is catalyzed by at least two members of the PLEIOTROPIC DRUG RESISTANCE (PDR) subclade of the ABCG family of ABC transporters (Borghi et al 2015): loss of ABCG36/PDR8/PEN3 Bartel 2009, Lu et al 2015) and ABCG37/PDR9/PIS1 , Ruzicka et al 2010 increases sensitivity to IBA, but not IAA.…”
Section: Novel Roles For Abc Transporters In Iba Transport?mentioning
confidence: 51%
See 2 more Smart Citations
“…Independent IAA and IBA transport catalysts are also supported by the finding that neither NPA nor the competitive auxin inhibitor, TIBA (2,3,5-triiodobenzoic acid), blocks IBA transport (Rashotte et al 2003, Liu et al 2012. Genetic approaches in Arabidopsis support the idea that IBA efflux from root cells is catalyzed by at least two members of the PLEIOTROPIC DRUG RESISTANCE (PDR) subclade of the ABCG family of ABC transporters (Borghi et al 2015): loss of ABCG36/PDR8/PEN3 Bartel 2009, Lu et al 2015) and ABCG37/PDR9/PIS1 , Ruzicka et al 2010 increases sensitivity to IBA, but not IAA.…”
Section: Novel Roles For Abc Transporters In Iba Transport?mentioning
confidence: 51%
“…Two independent studies support this concept (Rashotte et al 2003. Liu et al 2012; however, only one study verified the identity of the transported radiotracer as IBA (Liu et al 2012).…”
Section: Novel Roles For Abc Transporters In Iba Transport?mentioning
confidence: 97%
See 1 more Smart Citation
“…The simultaneous presence of unusual chemicals, e.g., 5-BDPU or 6-BDPU, plus auxin, has been described to promote adventitious rooting, reducing the disadvantages of a treatment with auxin alone (Ricci et al 2006;Brunoni et al 2014). To enlarge the action spectrum of these urea derivatives to commercial and/or environmental important species, but also to extend the knowledge on their morphogenic roles, they were presently used in in vitro micropropagated cuttings of Ceratonia siliqua L. Indole-3-butyric acid, i.e., the endogenous precursor of IAA (Liu et al 2012, and references therein), is useful in many culture systems to improve AR formation when applied exogenously, alone or in combination of a little amount of cytokinin. By the use of this hormone, present results showed that the simultaneous supplementation of IBA with 5-BDPU enhanced carob adventitious rooting.…”
Section: Discussionmentioning
confidence: 99%
“…In this plant and culture system, the gene expression occurs in both AR initiating cells and xylogenesis initiating cells, and is independent of exogenous IBA (Liu et al 2012;Della Rovere et al 2015). There is no information about a possible enhancing effect of 5-BDPU, and other similar urea derivatives, on the expression/activity of this auxin influx carrier.…”
Section: Xylogenesis Is a Competitive Program To Rhizogenesis In Caromentioning
confidence: 94%